Recent insights into the relationship between airway inflammation and asthma. - Siva, R; Berry, M; Pavord, I (2003)
There have been important recent advances in our understanding of the relationship between eosinophilic airway inflammation and airway dysfunction. Observational studies have shown that eosinophilic airway inflammation is not always present in asthma nor is it an exclusive feature of asthma. Its presence seems to be more closely linked to the presence of corticosteroid responsive airways disease and the occurrence of severe exacerbations than the presence of symptoms or the extent of airway dysfunction--indeed recent evidence suggests that in asthma these features may be more closely linked to the site of localisation of mast cells in the airway wall. One implication of this new understanding of the significance of eosinophilic airway inflammation is that it predicts that measuring airway inflammation might provide information that it is not readily available from a more traditional clinical assessment, and that patients might do better if this information is available. Recent studies support this view, showing a marked reduction in asthma exacerbation in patients with moderate to severe disease who are managed with reference to markers of airway inflammation as well as symptoms and simple tests of airway function. The development of new agents that have the potential to modulate specific aspects of airway inflammation, together with refinements in non-invasive techniques to assess the efficacy of these agents offers the prospect of further refining our understanding of the role of this aspect of the inflammatory response in asthma and other airway diseases.